Strands of diversity in Library and Information Science graduate curricula - Alajmi, Bibi M.; Alshammari, Israa (Malaysian Journal of Library and Information Science, 2020)
This study investigates the current coverage and treatment of strands of diversity in Library and Information Science (LIS) graduate curricula by examining 19 American Library Association (ALA) accredited Master of Library and Information Science (MLIS) programmes. The purpose is to analyze the depth and breadth of diversity-related topics in LIS programmes to determine the emphasis that LIS educators place on diversity-related content in the relevant coursework. Diversity-related topics were identified and categorized based on the published literature, and the contents of 84 course syllabi were examined. The findings show that while diversity-related topics are not prioritized in LIS programmes at present, the relevant content in curricula is increasing at a slow but significant rate. Diversity-related courses prepare aspiring librarians and information professionals to work with different cultural groups, young adults, and children. However, there is little interest in providing equitable services to minority groups in terms of gender and race/ethnicity, and people with disabilities. The findings of this study can provide a practical roadmap and useful insights for LIS educators, researchers, and practitioners.